The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1002/chem.201504618
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic Vinylidene Complexes and Azavinylidene Complexes by Formal [4+2] Cyclization Reactions

Abstract: Reactions of the hydrido-butenylcarbyne complex [OsHCl2(≡CC(PPh3)=CHEt)(PPh3)2]BF4 (1) with nitriles RC≡N (R=2-cyclopropyl-2-oxopropyl, 3-amino-2-oxobutyl) lead to six-membered cyclic vinylidene complexes 3 and azavinylidene complexes 4, that is, iso-osmapyridiniums. Treatment of 1 with excess 2-formylbenzonitrile at reflux temperature in CHCl3 in the presence of air produces a fused osmapyridinium 8, which is first oxidized to the tricyclic iso-osmapyridinium derivative 7, then to iso-osmapyridinium 9, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 100 publications
2
18
0
Order By: Relevance
“…For example, titanocene vinylimido complexes reacted readily with unsaturated organic substrates (ketones, nitriles, and imines) to form titana‐2,5‐dihydropyrimidines . In our previous work, we showed that osmapyridinium and iso‐osmapyridinium were obtained by reactions between osmium hydrido alkenylcarbynes and nitriles. In the present case, heterocumulene was used as the precursor in the formal [4+2] cyclization to access the metal‐bridged osmacycles that contain main‐group heteroatoms.…”
Section: Resultsmentioning
confidence: 99%
“…For example, titanocene vinylimido complexes reacted readily with unsaturated organic substrates (ketones, nitriles, and imines) to form titana‐2,5‐dihydropyrimidines . In our previous work, we showed that osmapyridinium and iso‐osmapyridinium were obtained by reactions between osmium hydrido alkenylcarbynes and nitriles. In the present case, heterocumulene was used as the precursor in the formal [4+2] cyclization to access the metal‐bridged osmacycles that contain main‐group heteroatoms.…”
Section: Resultsmentioning
confidence: 99%
“…As ulfur can be abstracted on treatment with CuCl to furnish the unusualm etallapyridyne species 50.T he aromaticity of the metallapyridine and metallapyridyner ings was also established by ASE and NICS value calculations. [184] Some related aromatic speciesh ave also been prepared including iso-osmapyridiniums, [185] as well as metallapyrimidines and metallapyrimidiniums, [186][187][188] in whicht wo Na toms are includedi nt he six-membered metallacycles.…”
Section: Metallabenzynesmentioning
confidence: 99%
“…Some related aromatic species have also been prepared including iso‐osmapyridiniums, as well as metallapyrimidines and metallapyrimidiniums, in which two N atoms are included in the six‐membered metallacycles.…”
Section: Heterometallabenzenesmentioning
confidence: 99%
“…Boger and co‐workers reported the inverse electron demand Diels‐Alder reactions of 1,2,4,5‐tetrazines with dienophiles [64] . In 2009, Xia and co‐workers synthesized osmapyridine and osmapyridinium complexes via a [4+2] cycloaddition reaction between 1‐metalla‐1,3‐dienes and nitriles (Scheme 1b) [65–67] . However, the application of Diels‐Alder reaction to transition‐metal involved dinitrogen activation has never been reported.…”
Section: Introductionmentioning
confidence: 99%